Development of E-LKPD Guided Inquiry Web Augmented Reality Biodiversity Material Based on Nepenthes Variation to Improve Critical Thinking Abilities and Psychomotor Skills of E-phase students - Djoko Martono; Suyitno Aloysus (Riviera Publishing, 2025)
This study developed a Guided Inquiry e-LKPD assisted by Web Augmented Reality (WebAR) on biodiversity material based on Nepenthes variations, aiming to enhance critical thinking skills and psychomotor abilities of Phase-E students. The product supports questioning, investigating, and constructing knowledge through 3D visualization of Nepenthes in real environments. A modified Borg & Gall R&D method was applied, with trials at MAN 2 Kota Semarang using a one-group pretest–posttest design. Instruments were expert-validated with very high scores. MANOVA analysis indicated a significant effect of WebAR on improving both critical thinking and psychomotor skills, simultaneously and separately. ANOVA and t-tests confirmed significant differences in learning outcomes between experimental and control groups, with greater improvement in the experimental group. The WebAR-based e-LKPD proved effective in strengthening cognitive aspects and psychomotor skills through interactive learning.